Initial-State Temperature of Light Meson Emission Source From Squared Momentum Transfer Spectra in High-Energy Collisions - Wang, Qi; Liu, Fu-Hu; Olimov, Khusniddin K. (Frontiers in Physics, 2021)
The squared momentum transfer spectra of light mesons, π^0, π^+, η, and ρ^0, produced in high-energy virtual photon-proton (γ^* p) → meson + nucleon process in electron-proton (ep) collisions measured by the CLAS Collaboration are analyzed by the Monte Carlo calculations, where the transfer undergoes from the incident γ^* to emitted meson or equivalently from the target proton to emitted nucleon. In the calculations, the Erlang distribution from a multi-source thermal model is used to describe the transverse momentum spectra of emitted particles. Our results show that the average transverse momentum (p_T) and the initial-state temperature (T_i) increase from lower squared photon virtuality (Q^2) and Bjorken variable (x_B) to higher one. This renders that the excitation degree of emission source, which is described by p_T and T_i, increases with increasing of Q^2 and x_B.